UPAYA MENINGKATKAN PENGUASAAN MUFRODAT BAHASA ARAB MELALUI METODE BERNYANYI DI KELAS VII A MTs N DONOMULYO KULON PROGO (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
The research aims at improving the student's learning achievement in Arabic learning by implementing Singing methode. The subject of this research were students of class VII A that consists of 21 students at Madrasah Tsanawiyah Negeri (MTsN) Donomulyo Nanggulan Kulon progo during the even semester in academic year of 2014/2015. The data analysis is the quantitative descriptive by counting on the average valve or mean from students’score. The product of this research is control mufrodat, the students class VII A on Arabic Language subject implementing singing method getting increase on the first cycle, students’ activities are categorized enough on 55,04 %, the second cycle increase better 70,87 % and on the third cycle that is categorited good on 81,92%.